The logistical episteme: Tracing the location of warehousing industries in Malaysia - Brett Neilson; Ned Rossiter (Work Organisation, Labour and Globalisation, 2025)
The concept of the ‘logistical episteme’ – the systemic organisation of practices, technologies and discourses geared toward the optimisation of efficiencies and value extraction – is crucial for understanding how contemporary capitalism reconfigures labour and geopolitics around computational power. This article explores the emergence of the logistical episteme by tracing the historical development of location theory and its integration with contemporary supply chain management. It highlights how algorithmic models and software shape the production of space and circulation of capital, with a focus on the case of warehousing industries in Malaysia. This approach allows an analysis of how the logistical episteme functions as a political technology, governing labour forces and mobilities, and corroding traditional notions of place.